Knee valgus in self-initiated vertical jump landings: developmental and gender comparisions - Russell, P. J.; Swartz, E. E.; Decoster, L. C.; Croce, R. V. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The study examined gender and developmental differences in knee valgus angle and external knee valgus moment at the time of maximal vertical ground reaction force (MGRFz) in self-initiated vertical jump (VJ) landings. Fifty-six subjects grouped by age (pre-pubescent (8-11 yrs); post-pubescent (19-29 yrs)) and gender jumped for a ball set at 50% of their maximum VJ height then landed on two feet with only their dominant foot on the force plate. Statistical analyses of motion analysis (3-D) and GRF data showed that children had greater valgus angles (p = .003) and moments (p = .026) at MGRFz compared to adults. Females had greater (p = .016) valgus moments than males, but similar valgus angles at MGRFz. It will be important to ensure that as both boys and girls progress through puberty they develop an ability to offset high valgus moments and land with good lower extremity alignment